Mistisisme Baru: Teilhard De Chardin - Gunardi, Andy (Bina Nusantara University, 2015)
Modernism today needs a new approachment in action and faith. Mysticism in the past is not sufficient to fulfil the needs today. The ways how to be faithfull through praying, and leaving the world should be transformed. Teilhard de Chardin, even lived in the 19th century, has had tought beyond his era. Today his idea and the way of his mysticism have a place. He wanted to unify all spiritual experiences in the past with modernism which has desire to know more the knowledges about earth. He tried to bring the science in as an effort to know more God and to love Him.His mysticism uses the daily life as a part of praying and a place to meet God. This study was based on a survey of young children and also consulting assistance to two students for 6 months. The method used is qualitative as well as quantitative. Mysticism associated with the dimensions of spiritual and also the dimension outside the spiritual. Mysticism is the driving force of love. Love unites two persons, namely God that exceeds any and all humans. Love relationship could be established both in spirit and the relationship of human with the world.